STRATEGI PEENINGKATAN PENERIMAAN PAJAK KENDARAAN BERMOTOR ALAT BERAT DI KABUPATEN INDRAGIRI HULU - Muhamad Idrus Amin; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Heavy vehicle motor vehicle tax in Indragiri Hulu Regency has decreased from the last 3 years. The purpose of this study is to make a strategy carried out by the Management of Rengat Revenue Management in increasing tax revenue for heavy equipment vehicles. Disseminate factors that hinder the strategy of increasing the tax revenue of heavy motor vehicles in the Revenue Management Unit in Indragiri Hulu Regency. The theoretical concept used is the Concept of Increasing Tax Revenue Strategy According to Sitorus in (Haerah, 2017: 266). This study uses descriptive qualitative methods. From the results of the study, it was found that the Strategy for Increasing Tax Revenues of Heavy Equipment Motor Vehicles in Indragiri Hulu Regency was not optimal due to inhibiting factors in the form of Direct Billing Process, Non-Comprehensive Counseling, MK Decision Regarding Heavy Equipment Tax, Lack of Public Trust in the Government and Lack of Utilization of IT (Information and Technology) in Tax Payments. Keyword: Improvement Strategy, Tax